(untitled) (Agroindustrial Science, 2024)
Soursop is a tropical fruit of economic importance in Mexico, however, there is scarce research on its nutrition. The aim of this study was to evaluate the foliar nutrient concentration in the vegetative state and to compare the nutritional diagnosis between the Kenworthy Balance Index (KBI) and Deviation from Optimum Percentage (DOP) in the soursop crop. The foliar concentration of N, P, K, Ca, Mg, Mn and B presented lower values than the reference standard. It was found concordance between KBI and DOP indices for the diagnosis in 91% of the orchards; the nutrients N, P, K, Ca, Mn and B were deficient in all orchards and excessive Cu (in 33% of the orchards), Fe and Zn (in 8% of the orchards respectively). However, the diagnosis of Mg, Fe, Cu and Zn in some orchards was contradictory due their adequate ranges with the KBI and deficient with the DOP. In general, with the two indices 25% of the orchards coincide with the decreasing order of the nutrients P<K<Ca<N<Mg<Mn<B<Zn<Fe<Cu. Although there were some similarities and differences in the nutritional diagnosis among KBI and DOP, the specific nutritional needs of each soursop orchard must be supply.